Performance of mustard varieties under irrigated area of Jaisalmer - Meena, OP; Chaturvedi, Deepak; Meena, RH; Khinchi, SK (Annals of Agricultural Research, 2014)
Total 180 Front Line Demonstrations (FLDs) on mustard varieties 'Bio-902' and 'Laxmi' were conducted at farmer's fields in irrigated area of Jaisalmer district during rabi 2005-06 to 2011-12. On an average, 23.6% higher seed yield was recorded under demonstrations than the farmers traditional practices. The extension gap, technology gap and technology index were 264 kg/ha, 486 kg/ha and 26.7%, respectively. An additional investments of Rs. 1668/ha coupled with scientific monitoring of demonstrations and non-monetary factors resulted in additional return of Rs. 5288/ha. Fluctuating minimum support price of mustard during different years influenced the economic returns per unit area. On seven years average basis incremental benefit cost ratio was 3.16.